Fatigue in cancer - Armes, Jo; Krishnasamy, Meinir; Higginson, Irene (Oxford University Press, 2004)
Provides a comprehensive review of the key issues involved in the research and practical application of current evidence and best practice guidelines for addressing cancer-related fatigue. An international group of contributors draw together core topics relating to this complex area of cancer management, focusing on issues of definition, patho-physiology, treatment related variables and the psychological, social and emotional impact on patients, families and carers. The book contributes a multi-disciplinary overview of a problem increasingly overlooked by cancer scientists, researchers, and clinicians.